Pengembangan Sadar Wisata Melalui Strategi Pentahelix Bagi Masyarakat Desa Wonosalam, Jombang - Huda, Syamsul; Wardaya, Wirya; Anitasari, Dwi (CV. ITTC INDONESIA, 2021)
Wonosalam is in a very the villages in Wonosalam District, Jombang Regency, East Java Province. Wonosalam Village has numerous business potentials which will be developed into holidaymaker destinations, each natural and artificial tourism. the aim of developing a tourist village is to extend growth and preserve the surroundings in an area. The involvement of the encircling community within the method of developing a tourist village will empower the community to create the village in a cooperative way. The existence of tourist destinations can not be separated from the role of pentahelix in the development of tourist villages. it's hoped that with the increasing role of the pentahelix actor, it will improve the event of its holidaymaker village. the upper the role of pentahelix actors (government, academics, business people, mass media, and also the community) in village development, the bigger the probabilities of the village changing into a developed and developing tourist village.